The use of miltefosine in the management of refractory Acanthamoeba keratitis. Issue 4 (August 2018) - Tavassoli, Shokufeh; Buckle, Miranda; Tole, Derek; Chiodini, Peter; Darcy, Kieren
Abstract: Acanthamoeba keratitis (AK) is a sight threatening infection most commonly affecting contact lens wearers. The authors report a case of intractable A.polyphaga and A.castellanii, with extensive intraocular spread, managed using oral miltefosine. A 59-year old male contact lens wearer was referred to the tertiary corneal service at Bristol Eye Hospital. Vision was hand movements on the left and 6/6 on the right. Clinical examination was consistent with left AK (confirmed by corneal scrape). Management included biguanide (polyhexamethylene biguanide (PHMB) 0.02%, later 0.06%) and diamidine (hexamidine 0.1%). Further treatment included imidazole (guttae voriconazole, oral posaconazole) and fortified biguanide (chlorhexidine 0.2%). Therapeutic PKP was performed. Microscopy revealed Acanthamoeba throughout host stroma. Corneal scrape and anterior chamber tap revealed persistent infection with Acanthamoeba . Intracameral voriconazole was administered twice. Clinically there was scleritis, with concerns regarding posterior segment involvement. There was a severe necrotic keratitis with almost complete corneal melt, requiring enucleation. Oral miltefosine was commenced to reduce the risk of transmission of Acanthamoeba beyond ocular structures at the time of the enucleation. Histopathological analysis detected A.polyphaga and A.castellanii in vitreous but not retina, choroid or optic nerve suggesting that infection had not progressed posteriorly through the ocular structures and the central nervous system was not involved. The use of miltefosine as a component of combination anti-parasitic therapy is associated with long-term survival in cases of Acanthamoeba infection of the central nervous system. This case reports its first systemic use in the United Kingdom in a case of severe intractable AK with intraocular spread.